(untitled) (Culturas Científicas, 2025)
Given the multiplicity of interpretations of quantum mechanics that give rise to very different ontologies, it is worth asking whether it is possible to find criteria with some empirical basis that make some interpretations preferable to others. If empirical evidence were found for the existence of quantum systems in the brain such as those necessary to adopt a form of panpsychism that resolves the problems of combination of subjects, qualities, and structures recognized since the time of William James, their underlying ontologies would be favored by allowing us to account for our conscious experiences. Quantum panprotopsychism has proven particularly well-suited to addressing the combination problems of panpsychism. It is based on an ontology of states and events with clearly identified physical and phenomenal counterparts and would therefore be recognizable if these physical elements were part of brain function.. Such an ontology could provide criteria for preferring certain quantum interpretations over others. Here we will analyze the interpretations that would be favored or challenged by the ontology resulting from this form of panprotopsychism.